Complex Analysis of Morphological Characters of Gamasid Mite Varroa destructor (Parasitiformes, Varroidae) - Akimov, I.A.; Benedyk, S.V.; Zaloznaya, L.M. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2004)
Проведено исследование сезонной изменчивости клеща V. destructor. Установлено, что летняя генерация клещей характеризируется наибольшей дисперсией признаков, а зимняя — наибольшей их стабильностью. Не удалось выделить комплекс морфологических признаков, который бы позволял с высоким уровнем достоверности идентифицировать определенный фенотип клеща. Выявлена значитель¬ная стабильность морфологических признаков V. destructor во времени. Подтверждено, что по среднему значению длины и ширины тела, паразитирующий на медоносной пчеле Apis mellifera Linnaeus в Украине, клещ варроа относится к описанному корейскому гаплотипу Varroa destructor Anderson et Trueman, 2000. The study of seasonal variability of mite V. destructor was carried out. The summer generation of mites appears to be characterized by the largest morphological variability whereas the winter one has stable characters. We failed to evolve the complex of morphological characters that would allow us to identify, with high level of reliability, certain phenotype of the mite. Significant stability of morphological characters of V. destructor in the course of time was determined. The mean values of the length and width of the body allow to consider the Ukrainian population of Varroa mite, which parasitize the honey bee Apis mellifera Linnaeus, as the Korean haplotype of Varroa destructor Anderson et Trueman, 2000.